Budidaya Tanaman Cabai Rawit (Capsicum frutescens L.) melalui Pemanfaatan Hormon GSA (Giberelin Sitokinin Auksin) Organik - Suhita, Cahyaningtyas Putri; Nurafian, Dimas Asyarif; Setyaningrum, Desy (Jurnal Kridatama Sains dan Teknologi, 2024)
The consumption of cayenne pepper tends to increase every year which is not balanced with the amount of national production, so a solution is needed so that the productivity of cayenne pepper can increase. Increasing productivity can be done through the use of organic fertilizers, namely GSA (Gibberellin Cytokinin Auxin). GSA stimulates the growth of roots, stems, leaves, branches, flower and fruit development, prevents aging, and helps seed germination. The purpose of this study was to determine the cultivation of cayenne pepper with the addition of GSA (Gibberellin Cytokinin Auxin) hormones and to analyze the farming efforts of cayenne pepper cultivation. This research was conducted in Pager Jurang Hamlet, Kepuharjo Village, Sleman Regency, Special Region of Yogyakarta. The research methods include field practice, observation and interviews. Conventional cayenne pepper cultivation activities on beds include preparation of planting media, sowing, planting, maintenance, harvesting, and post-harvest. Cultivation activities of cayenne pepper through the use of GSA hormones. Environmental conditions have a temperature of 22.5°C-28.4°C, humidity of 62.5%-85.2%, light intensity of 1845-3270 lux, altitude of 699 meters above sea level, and regosol soil type. The productivity of cayenne pepper is 62.26 kg during 14 harvests. The selling price of cayenne pepper tends to fluctuate by IDR 34,000/kg (April), IDR 23,000/kg (May), IDR 33,000/kg (June), and IDR 43,000/kg (July). Analysis of cayenne pepper cultivation farming can be said to be feasible or profitable with an R/C ratio of 1.17; B/C ratio of 0.17; and ROI of 17%. The farming ratio can be greater if the selling price is above the BEP price